NATIVE LANGUAGE INTERFERENCE IN ENGLISH ADJECTIVE ORDERING: A STUDY OF SENIOR SECONDARY SCHOOL STUDENTS IN NIGERIA - Abubakar, Nasiru Bello; Hassan, Isyaku; Yusof, Norma Binti; Yusof, Akmah Binti (IJRDO- Journal of Educational Research, 2017)
Many studies revealed that non-native speakers of English language face difficulties inunderstanding the correct order of adjectives, especially when there is more than oneadjective qualifying a noun. This is a case of interference which, although criticized byseveral authors, referring to the influence of one language on another. This study aims toexamine native language interference in English adjective position and order among Englishnon-native speakers. The study employed a qualitative approach, in which test and erroranalysis were used to collect and analyze data respectively. The participants comprised finalyear students of Government Secondary School Dala, Kano-Nigeria. A sample of 20 studentswho are Hausa native speakers was purposively selected using typical sampling strategy. Thefindings revealed that the students’ native language influences their English adjectiveposition and order. Altogether, the students made 66 errors out of 200 responses theyprovided across English adjective position and order. These errors might reflect pooracademic performance amongst the students. Therefore, the students should develop bothEnglish speaking, and reading culture and their teachers should encourage them, sincelanguage learning requires constant practice.